Production pepper cultivated with stone dust and manure in semi-arid region (Research, Society and Development, 2020)
The research was carried out aiming to verify the effect of rock powder and bovine manure as natural sources for fertilization and nutrition of the pepper culture (Capsicum annuum L. cv. All Big). The experiment was carried out in the seedling nursery of the Federal Institute of Education Science and Technology of Paraíba - IFPB, Campus Sousa, São Gonçalo Unit during the period from September 2014 to August 2015. The experimental design used was in randomized blocks (DBC ) with 10 treatments and 4 repetitions, totaling 40 experimental units. The treatments were as follows: T1 = control (soil), T2 = soil + manure + rock powder (1: 1: 1); T3 = Soil + Dung + Rock Dust (2: 1: 1); T4 = Soil + Dung + Rock Dust (2: 2: 1); T5 = Soil + Dung + Rock Dust (2: 2: 2); T6 = Soil + Dung + Rock Dust (3: 1: 1); T7 = Soil + Dung + Rock Dust (3: 2: 1); T8 = Soil + Dung + Rock Dust (3: 2: 2); T9 = Soil + Dung + Rock Dust (3: 3: 2); and T10 = Soil + Dung + Rock Dust (3: 3: 3). Plant height, fresh shoot weight, fresh root weight, dry shoot weight, dry root weight, fruit length, fruit diameter, fresh fruit weight, dry fruit weight, total production and commercial production. The treatments tested significantly influenced the variables: dry and fresh root material, fresh and dry aerial part, fruit length (second harvest) and dry fruit mass (second harvest). The association of rock powder with bovine manure, natural by-products, rich in nutrients essential to the development and production of plants, presents itself as a potential alternative for use in agriculture. The T8 treatment provided greater commercial production with fruits in the commercial standard.